(untitled) (ACME, 2025)
This paper discusses the question of multiple Greek citizenships in the imperial age by taking, as a case study, selected passages from the Bithynian orations of Dio Chrysostom. These passages shed light on the public and institutional settings and contexts in which acquired citizenships, far from being perceived simply as honorific titles, caused difficulties and set limits and challenges for their holders: the case of Dio and his sophisticated attempts to “juggle” before the assemblies and councils of Bithynian cities, (often rival cities), is a clear example of this.